Social Protection as a Strategy for Global Economic Growth: An Empirical Analysis - Septiyanti, Ratna (Penerbit Goodwood, 2024)
Abstract Purpose: This study aims to empirically test the role of social protection on economic growth internationally. Methodology: The sample used was 71 countries worldwide. Data were gathered from the International Monetary Fund (IMF) database and analysed with Ordinary Least Square (OLS) analysis. Results: A significant positive effect of social protection aspects on economic growth was found. Limitations: This study is limited to 71 countries because of the data limitation. Future researches are expected to expand the sample and observation period. Contribution: This study provides a comprehensive understanding of social protection's role in fostering an environment conducive to economic growth, while ensuring equitable resource distribution and sustainable accounting practices. The results of this study are expected to be used as a basis for formulating regulations and compiling policies for harmonization of accounting regulations at the international level.